Genome-Scale CRISPR screen identifies LAPTM5 driving lenvatinib resistance in hepatocellular carcinoma. Issue 4 (3rd April 2023) - Pan, Jiaomeng; Zhang, Mao; Dong, Liangqing; Ji, Shuyi; Zhang, Juan; Zhang, Shu; Lin, Youpei; Wang, Xiaoying; Ding, Zhenbin; Qiu, Shuangjian; Gao, Daming; Zhou, Jian; et al.
ABSTRACT: Drug resistance has greatly limited the clinical efficacy of lenvatinib in hepatocellular carcinoma (HCC). However, the underlying molecular mechanisms of lenvatinib resistance remain largely undetermined. Further in-depth exploration of mechanisms underlying lenvatinib resistance is still required for the majority of HCC patients. In this study, an integrated unbiased whole-genome CRISPR-Cas9 screen with database analysis indicated LAPTM5 (lysosomal protein transmembrane 5) as the critical contributor to lenvatinib resistance in HCC. We revealed that LAPTM5 could promote intrinsic macroautophagic/autophagic flux by facilitating autolysosome formation to drive lenvatinib resistance. The upregulation of LAPTM5 in HCC was induced by both DNA hypomethylation and driver mutations like TP53 . Inhibition of autolysosome formation by either hydroxychloroquine (HCQ) or LAPTM5 abrogation worked synergistically with lenvatinib to inhibit tumor growth. In HCC cell lines, patient-derived primary cell lines and organoids, as well as human HCC xenografts and immunocompetent mouse HCC model, the close association between LAPTM5 and sensitivity to lenvatinib was consistently verified. Importantly, in clinical HCC samples, where lenvatinib was used as the first line or adjuvant therapy, LAPTM5 expression negatively correlated with lenvatinib sensitivity, implying it as a biomarker to predict patient response to lenvatinib. In conclusion, the combinational therapy targeting autophagy represented a promising strategy to overcome lenvatinib resistance in HCC, and LAPTM5 expression could provide potential guidance for clinical interference. Abbreviations: cld-CASP3: cleaved caspase 3; cld-PARP: cleaved PARP; DTP: drug tolerant persister; GO: Gene Ontology; GTEx: The Genotype-Tissue Expression; HCC: hepatocellular carcinoma; HCQ: hydroxychloroquine; IC50: half maximal inhibitory concentration value; KEGG: Kyoto Encyclopedia of Genes and Genomes; LAPTM5: lysosomal protein transmembrane 5; NT: non-targeting; PDC: patient-derived primary cell lines; PDO: patient-derived primary organoid; TCGA: The Cancer Genome Atlas.